Different methods to measure canine rotation - Neam F Agha; Neam R Al–Saleem (Al-Rafidain Dental Journal, 2006)
Aim: Demonstration of a new method which is liner measurement to record the amount of canine rotation after orthodontic treatment, in addition to the ordinary angular method for measuring canine rotation. Materials and Methods: Forty five patients (20 males and 25 females) were selected: Those need extraction of the first premolars for correction of malocclusion. Their age varied from 12–23 years. A study model was taken for them pre and post treatment, then measurements were done directly on the cast and other measurements indirectly converted on a paper to measure other variables. Results: There were no significant differences among age groups and between the sexes for the angular and linear methods. Also, there was insignificant canine rotation in the mesial or distal sides toward or away from the reference line within the different groups; this clearly seen in the linear method. In the angular method, also canine rotation can be seen within the age groups but not demonstrated the side of rotation like the linear method. Conclusion: Canine rotation occur within the treatment work in the two methods of measuring canine rotation, but this research proved that the linear direct measurement which is the new method followed in this work was more beneficial and accurate for clinical work than the indirect angular measurements.